The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s1388-9842(03)00060-6
|View full text |Cite
|
Sign up to set email alerts
|

D‐Ribose improves diastolic function and quality of life in congestive heart failure patients: a prospective feasibility study

Abstract: Patients with chronic coronary heart disease often suffer from congestive heart failure (CHF) despite multiple drug therapies. D-Ribose has been shown in animal models to improve cardiac energy metabolism and function following ischaemia. This was a prospective, double blind, randomized, crossover design study, to assess the effect of oral D-ribose supplementation on cardiac hemodynamics and quality of life in 15 patients with chronic coronary artery disease and CHF. The study consisted of two treatment period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 17 publications
3
59
0
Order By: Relevance
“…Health-related measures were used in 46 studies. In the majority (52%), the measure of choice was the 36-item Short-form Health Survey (SF-36) or some subscale(s) of the SF-36 (24 studies) [61][62][63][64][65]10,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. In six studies, this was the only QoL measure used.…”
Section: Resultsmentioning
confidence: 99%
“…Health-related measures were used in 46 studies. In the majority (52%), the measure of choice was the 36-item Short-form Health Survey (SF-36) or some subscale(s) of the SF-36 (24 studies) [61][62][63][64][65]10,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. In six studies, this was the only QoL measure used.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, elevation of tissue ATP levels with Rib/Ade may be of value in the postischemic brain. In fact, Rib has been used to improve postischemic cardiac function in vitro, in vivo, and in humans (Zimmer, 1998;Omran et al, 2003;Shecterle et al, 2010). Although Ade has to be administered with a xanthine oxidase inhibitor (Watts et al, 1974;Simmonds, 1986) to prevent its conversion to an insoluble metabolite, this may be beneficial (Phillis et al, 1995) because it would prevent the formation of nonsalvageable xanthine, thereby providing greater substrates for the purine salvage pathway in the post-ischemic brain.…”
Section: Temperature Dependence Of the Atp/amp Ratio And Ampk Activitymentioning
confidence: 99%
“…Pre-clinical studies have demonstrated the recovery benefits in depressed high-energy phosphates with D-ribose as well as functional improvements in the myocardium following ischemia and in isolated skeletal muscle [1][2][3][4]. Clinically, congestive heart failure patients have experienced improvements in their diastolic dysfunction, ventilatory efficiency, a better quality of life, and improved physical function activities when taking oral D-ribose [5][6][7]. The benefits in sports medicine have not been as obvious.…”
Section: Introductionmentioning
confidence: 99%